SYNTHETIC AND ANALYTICAL ACCOUNTING OF LABOR REMUNERATION - Klara Abdullayevna Yusupova (European Science Publishing, 2025)
This article examines the synthetic and analytical accounting of labor remuneration as a crucial component in financial management and organizational efficiency. It explores the theoretical foundations of wage accounting and analyzes its practical applications within enterprises. The study emphasizes the importance of accurate payroll management for maintaining financial stability and ensuring compliance with labor regulations. Practical recommendations are provided to enhance the effectiveness of wage accounting systems in Uzbekistan’s economic context. The findings aim to support students and professionals in understanding and applying modern accounting practices to optimize labor cost management.
Keywords: Labor remuneration, synthetic accounting, analytical accounting, payroll management, financial stability, economic efficiency, wage systems.